Hydnobolites oaxacanus (Pezizales, Ascomycota), a new species from Mexico - de La Fuente, Javier Isaac; García-Jiménez, Jesús; Martínez-González, César Ramiro; Ayala-Vásquez, Olivia; Hernández Del-Valle, Juan Francisco; Sánchez-Florez, Marcos; Peña-Ramírez, Rafael (Phytotaxa, 2022)
Hydnobolites oaxacanus is described using molecular and morphological data. This new species is characterized by the whitish ascomata with orange spots, grey gleba, and 4-spored asci with ascospores of 17–45 × 15–20 µm. The new species differs from other American Hydnobolites such as H. californicum and H. cerebriformis by the number of ascospores per asci, and larger ascospore size and ornamentation. It is putatively associated with Quercus castanea in the Quercus-Pinus dry mixed forest. Photographs, descriptions, and molecular phylogeny of the ITS region are presented.